Aleksandra Kornhauser Frazer - utemeljiteljica izobraževanja za trajnostni razvoj - Pivec, Franci (Mednarodno inovativno poslovanje, 2009)
The article focuses on the work of Aleksandra Kornhauser Frazer in the area of education, especially the modernisation of science education and the informatization of schools and research activities in general. The article presents her part in the Delors Comission on Education for the 21st Century. Some of her most distinguished achievements are the methodology for cooperation between higher education, industry and research and her approaches towards innovation in higher education. All her basic concepts are merged into theory of education for sustainable development, whose co-founder she was on a global scale.
Keywords: cooperation between higher education and industry; Delors report; Delorsovo poročilo; education; education for sustainable development; innovative education; inovativno izobraževanje; izobraževanje; izobraževanje za trajnostni razvoj; kakovost visokega šolstva; quality of higher education; sodelovanje med visokim šostvom in industrijo; visoko šolstvo